Life after break up: The Impact of a breakup on mental health and coping strategies among college students - ISLAMIYAH, DWI NATASYA (Maliki Interdisciplinary Journal, 2026)
Breakups are one of the common emotional experiences faced by university students, particularly during early adulthood, a phase characterized by the exploration of interpersonal relationships and the search for personal identity. Although often considered a normal life event, numerous studies have shown that breakups can have significant impacts on mental health, including increased anxiety, depression, emotional stress, and even a decline in academic performance. This study aims to analyze in depth the impact of breakups on students’ mental health and to identify the coping strategies used to deal with these conditions. The method employed is a literature review with a descriptive qualitative approach, examining various scientific journals from universities in Indonesia that are openly accessible. Students who experience a breakup tend to suffer from emotional disturbances such as deep sadness, loss of motivation, decreased self-esteem, and difficulty concentrating. The coping strategies used by students include adaptive coping, such as emotional regulation, social support, and positive activities, as well as maladaptive coping, such as withdrawal and excessive rumination. Emotional regulation has been shown to be an important factor in accelerating the recovery of an individual’s psychological condition after a breakup. Social support from friends and family also plays a significant role in helping individuals cope with emotional distress.